Reward processing deficits arise early in familial frontotemporal dementia - Cryns, Noah G.; Hardy, Emily G.; Roy, Ashlin R. K.; Datta, Samir; Sokolowski, Andrzej; Sturm, Virginia E.; Kramer, Joel H.; Boxer, Adam L.; Miller, Bruce L.; Rosen, Howard J.; Perry, David C. (Frontiers in Neuroscience, 2024)
Reward processing involves evaluation of stimuli to inform what an individual works to pursue or avoid. Patients with behavioral variant frontotemporal dementia (bvFTD) often display reward processing changes, including insensitivity to aversive stimuli. It is unknown how early in the disease course reward changes are detectable. We recruited mutation positive (symptomatic and asymptomatic) and negative members of families with known mutations in progranulin (GRN), microtubule-associated protein tau (MAPT) and chromosome 9 open reading frame 72 (C9orf72). The sample included 4 groups: asymptomatic non-carriers (n = 34), asymptomatic carriers [Clinical Dementia Rating (CDR) 0, n = 16], mildly symptomatic carriers (CDR 0.5, n = 10) and bvFTD (sporadic and genetic, n = 45). A series of tasks utilized pleasant, unpleasant, and neutral olfactants to probe reward consumption and effort to obtain reward. A group by valence interaction showed unpleasant scent ratings were more positive in groups with greater disease severity [χ2(6) = 87.983, p < 0.001]. Mildly symptomatic carriers showed a small difference in ratings of pleasant and unpleasant stimuli, similar to bvFTD. In an effort task, where participants chose to avoid or receive scents, mildly symptomatic carriers and bvFTD chose to smell unpleasant scents more frequently than asymptomatic groups, with mildly symptomatic carriers exceeding bvFTD in their frequency of choosing to smell unpleasant scents. In this same task, motivated effort, determined by rate of button press, determined success at obtaining or avoiding scents. Success rate, calculated based on the number of responses where participants’ button presses exceeded an individual threshold set in a practice trial, differed across groups (p = 0.048), driven by mildly symptomatic carriers, who were consistently unsuccessful. There was a group difference in variability in button press rate across trials (p = 0.007), driven by mildly symptomatic carriers who showed less varied effort between scents. These findings suggest alterations to reward functioning can be detected early in bvFTD, even before meeting diagnostic criteria. These results may aid in identifying distinctive, initial reward changes in bvFTD that can facilitate early and accurate diagnosis and inspire efforts to identify anatomic underpinnings of early symptomatic changes.